Study on the Effect of the Ambient Temperature toward the Quality of Sleep - Wira Hidayat bin Mohd Saad; Khoo Chin Wuen; Masrullizam bin Mat Ibrahim; Nor Hashimah Binti Mohd Saad; Syafeeza Binti Ahmad Radz; Ahmad Sayuthi bin Mohamad Shokri; Mohd Safirin bin Karis (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Getting enough sleep at the right times can help in improving quality of life and protect mental and physical health. This study proposes a portable sleep monitoring device to determine the relationship between the ambient temperature and quality of sleep. Body condition parameter such as heart rate, body temperature and body movement was used to determine quality of sleep. All readings will be log into database so that users can review back and hence analyze quality of sleep. The functionality of the overall system is designed for a better experience with a very minimal intervention to the user. The simple test on the body condition (body temperature and heart rate) while asleep with several different ambient temperatures are varied and the result shows that someone has a better sleep for the temperature range of 23 to 28 degree Celsius. This can prove by lower body temperature and lower heart rate.